2001
DOI: 10.1039/b108568a
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent PEBBLE nanosensor for intracellular free zinc

Abstract: The development and characterisation of a fluorescent optical PEBBLE (Probe Encapsulated By Biologically Localised Embedding) nanosensor for the detection of zinc is detailed. A ratiometric sensor has been fabricated that incorporates two fluorescent dyes; one is sensitive to zinc and the other acts as a reference. The sensing components are entrapped within a polymer matrix by a microemulsion polymerisation process that produces spherical sensors that are in the size region of 20 to 200 nm. Cellular measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(81 citation statements)
references
References 26 publications
0
81
0
Order By: Relevance
“…Other sensors, such as magnesium, 19 calcium, 43 and zinc 24 sensors, which also rely on the binding of the metabolite the sensor is designed for, could potentially encounter the same problems. pH Measurements in Time and Space.…”
Section: Resultsmentioning
confidence: 99%
“…Other sensors, such as magnesium, 19 calcium, 43 and zinc 24 sensors, which also rely on the binding of the metabolite the sensor is designed for, could potentially encounter the same problems. pH Measurements in Time and Space.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work on both polyacrylamide-based and sol-gel based PEBBLE sensors also demonstrated that the matrix, as expected, prevented macromolecules such as proteins (e.g. bovine serum albumin) from diffusing through [27][28][29]. The matrix protected entrapped dyes from the intracellular environment, thus diminishing interference with the fluorescent properties of the dyes [25].…”
Section: Prevention Of Enzymatic Reduction Of Mb By the Matrixmentioning
confidence: 93%
“…These allow the analyte to permeate the matrix and interact with the indicator dye directly and selectively, thereby causing stimulation or quenching of fluorescence. Direct measurement PEBBLEs have been used for sensing H + [52], Ca 2+ [52], Mg 2+ [59], Zn 2+ [10] and glucose [60]. Sol-gel PEBBLEs are normally designed as dissolved gas sensors, and have been used for sensing dissolved molecular oxygen [57,58].…”
Section: Pebblesmentioning
confidence: 99%